2009
DOI: 10.1258/ijsa.2008.008213
|View full text |Cite
|
Sign up to set email alerts
|

Condylomata gigantea in a male transsexual

Abstract: As the incidence of genital warts increases, warts arising in the mouth, throat and other sites can occasionally be seen. Condyloma gigantea in genital sites are often reported, but literature on genital warts in transsexuals is rare. We present a case of C. gigantea in a 23-year-old male-to-female transsexual, whose warts arose on the transplanted skin of a neovagina and in the perianal region. We conclude that although C. gigantea can occur in transsexuals, the best way to treat it is not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…104 Lack of hair regrowth should be confirmed 3 months after the most recent laser session before proceeding with surgery. 105 Condyloma acumintata [106][107][108][109] and carcinomas [110][111][112][113][114][115] of the neovagina have been reported; referral for internal examination can be considered, especially for patients with prior external genital warts.…”
Section: Transgender Womenmentioning
confidence: 99%
“…104 Lack of hair regrowth should be confirmed 3 months after the most recent laser session before proceeding with surgery. 105 Condyloma acumintata [106][107][108][109] and carcinomas [110][111][112][113][114][115] of the neovagina have been reported; referral for internal examination can be considered, especially for patients with prior external genital warts.…”
Section: Transgender Womenmentioning
confidence: 99%
“…Reported treatments ranged from patient-administered methods podophyllotoxin or imiquimod, to physicianoperated methods, including CO 2 laser ablation, electrovaporization, surgical excision, and total colpectomy. [11][12][13][14][15][16][17][18] To our knowledge, this is the first case report of neovaginal warts successfully treated with TCA.…”
Section: Discussionmentioning
confidence: 76%
“…7 HIV and STIs have regularly been reported in MtF transgenders, but mostly in the (non-Western) commercial sex industry and pre-dominantly in the penile skinlined neovagina. [8][9][10][11][12][13][14] As a group, MtF transgenders exhibit high-risk behaviour for exposure to HIV and STIs in Latin-American, North-American and Asian research. 8 It has been reported that transgendersincluding our patient -frequently engage in unprotected sexual activities, because they are uncomfortable using a condom and condom negotiation is difficult for them.…”
Section: Discussionmentioning
confidence: 99%